ADORA2A-AS1 Restricts Hepatocellular Carcinoma Progression via Binding HuR and Repressing FSCN1/AKT Axis - Pu, Jian; Zhang, Ya; Wang, Anmin; Qin, Zebang; Zhuo, Chenyi; Li, Wenchuan; Xu, Zuoming; Tang, Qianli; Wang, Jianchu; Wei, Huamei (Frontiers in Oncology, 2021)
Background: Hepatocellular carcinoma (HCC) is one of the most aggressive malignancies. Increasing evidences revealed that long non-coding RNAs (lncRNAs) were frequently involved in various malignancies. Here, we explored the clinical significances, roles, and mechanisms of lncRNA ADORA2A-AS1 in HCC. Methods: The clinical significances of ADORA2A-AS1 in HCC were analyzed using RNA-seq data from TCGA project. The expressions of ADORA2A-AS1, FSCN1, MMP2, and BIRC7 in HCC tissues and cells were measured by qRT-PCR. CCK-8, EdU, caspase-3 activity assay, transwell migration and invasion assays, xenograft growth and metastasis experiments were performed to evaluate the roles of ADORA2A-AS1 in HCC. RNA pull-down, RNA immunoprecipitation, qRT-PCR, western blot, and RNA stability assay were performed to elucidate the mechanisms of ADORA2A-AS1 in HCC. Results: ADORA2A-AS1 was identified as an HCC-related lncRNA, whose low expression was correlated with advanced stage and poor outcome in HCC. Gain- and loss-of functional experiments demonstrated that ADORA2A-AS1 inhibited HCC cell proliferation, induced cell apoptosis, repressed cell migration and invasion, and repressed xenograft growth and metastasis in vivo. Mechanistically, ADORA2A-AS1 competitively bound HuR, repressed the binding of HuR to FSCN1 transcript, decreased FSCN1 transcript stability, and downregulated FSCN1 expression. The expression of FSCN1 was negatively correlated with ADORA2A-AS1 in HCC tissues. Through downregulating FSCN1, ADORA2A-AS1 repressed AKT pathway activation. Functional rescue assays showed that blocking of FSCN1/AKT axis abrogated the roles of ADORA2A-AS1 in HCC. Conclusion: Low expression ADORA2A-AS1 is correlated with poor survival of HCC patients. ADORA2A-AS1 exerts tumor suppressive roles in HCC via binding HuR and repressing FSCN1/AKT axis.